If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
((2*x)/3)*x-(5/6) = 0
((2*x)/3)*x-5/6 = 0
2/3*x^2 = 5/6 // : 2/3
x^2 = 5/4
x^2 = 5/4 // ^ 1/2
abs(x) = (5/4)^(1/2)
x = (5/4)^(1/2) or x = -(5/4)^(1/2)
x in { (5/4)^(1/2), -(5/4)^(1/2) }
| 2x^2-8x-56=0 | | 7x-2=-58 | | 5=7n-2 | | 3(x-10)-4=-6x-2 | | x-17=-12 | | -1=11+n | | 9x-13=-10+12x | | 9x-13=-10+12z | | x^16-2x^15-x^14+4x^13-x^11+x^10=0 | | 1-n=-2 | | -72=-18a | | (-x+4)(2x-1)= | | 12x^2-52x+35=0 | | 19k=-95 | | (45x^4y^10)/(9x^6y^6) | | 13=9x-5 | | 55-3T=103-7T | | 8x^2+60x-25=0 | | -14-x=-9 | | -117=-13m | | 195=13n | | -4(7-2q)+9q= | | m+14=21 | | 4n-18=42 | | (x+8)(x-2)=-24 | | 9x+9=9(x-4) | | p(p+8)=-7 | | 7n=-98 | | 1100=5c*2 | | 4(5x+8)=20x+32 | | -12=m-(-5) | | 2z/-9=-4 |